Future strategic plan analysis for integrating distributed renewable generation to smart grid through wireless sensor network: Malaysia prospect - Zahurul S.; Mariun N.; Grozescu I.V.; Tsuyoshi H.; Mitani Y.; Othman M.L.; Hizam H.; Abidin I.Z. (Elsevier Ltd, 2023)
Cost effectiveness; Developing countries; Electric power transmission networks; Integration; Internet protocols; Optical communication; Smart power grids; Surveys; Zigbee; Bi-directional communication; Building integrated photovoltaic; Communication infrastructure; Information andcommunicationtechnology; Smart gridcommunication; State-of-the art protocols; Tenaga Nasional Berhad; Wireless sensor network (WSNs); Wireless sensor networks